Critical thinking skills success in 20 minutes a day - Starkey, Lauren B., 1962-; LearningExpress (Organization); Overdrive.com. (New York Learning Express, 2015)
This e-book helps you become an effective critical thinker, one who is able to make sound decisionn and solve problems. Topics include the standardized exams that test your critical thinking skills; logical reasoning and deductive skills to eliminate wrong answers on multiple-choice tests, toubleshooting techniques to use on the job, and research and decision-making skills to use at home.
Recognizing a problem -- Defining a problem -- Focused observation -- Brainstorming with graphic organizers -- Setting goals -- Troubleshooting -- Finding resources -- Evaluating facts -- Persuasion techniques -- The numbers game -- Checking your emotions -- Deductive reasoning -- Errors in deductive reasoning -- Inductive reasoning -- Errors in inductive reasoning -- Distracting techniques -- Making judgment calls -- Explanation or argument? -- Critical thinking for exams -- Putting it all together.
Rev. ed. of: Critical thinking skills success in 20 minutes a day / Lauren Starkey.
Includes bibliographical references and index.
Keywords: Critical thinking -- Handbooks, manuals, etc; Thought and thinking; Problem solving; Decision making; Life skills; Electronic books